ICT and Resilience in Times of Crisis: What Do the Meso-Level Data Say? - Michael Polder; Irene Bertschek; Patrick Schulte (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Are ICT-intensive firms more resilient in times of crisis? We study this question by exploiting a novel and unique data set from the EU Micro-Moments Database. Covering 12 countries, 7 industries and the period from 2001 to 2010, the data allow us to distinguish between ICT-intensive and non-ICT-intensive firms within industries. We find evidence that during the crisis, ICT-intensive firms were hit less hard with respect to productivity and developing process innovations.
Keywords: 330